The Parliamentary Commissioner for Future Generations of Hungary and his Impact - Éva Tóth Ambrusné (Intergenerational Justice Review)
The Parliamentary Commissioner for Future Generations of Hungary is a fairly new and unique institution that was established in 2008. The Commissioner is provided with strong and very specific competences and powers to protect the interests of future generations. The publication of his first annual report1 to Parliament is a great opportunity to assess the effectiveness of the tools he can apply to facilitate intergenerational equity.